Regular COVID-19 Pandemic Containment in Communities: A Risk Governance Perspective - Li H; Zhang L; Wang L; Xu T (Dove Medical Press, 2021)
Huijie Li, Liwei Zhang, Long Wang, Tianjiao Xu School of Public Administration, Jilin University, Changchun, People's Republic of ChinaCorrespondence: Tianjiao XuJilin University, Changchun, People's Republic of ChinaTel +86 15764324495Email xtjjlu01@163.comAbstract: Post COVID-19, differentiated regular management in place of strict lockdowns is more favored as a feasible option for balancing economic resumption and pandemic control. China's transition experience shows that this stage came not easily, during which regional sporadic outbreaks could re-emerge. Actually, it is an ongoing process of identifying loopholes and refining the management. Based on the IRGC risk governance framework, this article analyzes these challenges in community involvement posed by the transition. The systematic examination of the whole risk chain would be conducive to contain the virus spread, lessen the pressure of communities for the battle and enhance future responses for a possible resurgence. Unlike the emergency mode with mass mobilized, during regular control periods, community becomes the critical frontline for suppressing COVID-19 but with limited manpower and resources. Still, it can serve as a transformation platform to motivate atomized residents to take responsibility or contribute. Notably, the health governance of all people never ends. With the increased knowledge of COVID-19, the progress of pandemic control, and the needed adjustments for behavioral responses, different communities should come up with more suitable options instead of rigid management back to the old days.Keywords: pandemic control experience, IRGC risk governance framework, China, COVID-19